Effects of dietary yeast β-1.3/1.6-glucans on oxidative stress biomarkers in hearts and livers of rainbow trout (Oncorhynchus mykiss Walbaum), European whitefish (Coregonus lavaretus L.), and grayling (Thymallus thymallus L.) - Tkachenko Halyna; Grudniewska Joanna; Kurhaluk Natalia (Fisheries & Aquatic Life, 2022)
The present study was performed to investigate the effects of dietary yeast β-1,3/1,6-D-glucans supplemented over a 14-day feeding period on liver and cardiac function and the oxidative mechanism underlying these effects. We assessed relevant lipid peroxidation and protein oxidation biomarkers, antioxidant defense indices [superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR), glutathione peroxidase (GPx), total antioxidant capacity (TAC)], and biochemical alterations [activities of aminotransferases (AT), lactate dehydrogenase (LDH), and succinate dehydrogenase (SDH), and levels of lactate (L) and pyruvate (P)] in rainbow trout, European whitefish, and grayling. The fish received a control diet and an experimental diet containing yeast β-1,3/1,6-D-glucans at a dose of 1% in the basal feed for 14 days. The results demonstrated enhancement in the phagocytic activity and phagocytic index in the groups fed β-glucans, compared to the control groups. In the groups fed β-glucans, the oxidative stress parameters such as lipid peroxidation, oxidatively modified proteins, and TAC did not vary significantly. The dietary β-glucans stimulated CAT and GPx activities in hepatic and cardiac tissues in comparison to the control group; however, a reverse trend was observed in the GR activity in these tissues.